First record of Turnera ulmifolia L. (Turneraceae) as introduced in Brazil - Rocha, Lamarck (Phytotaxa, 2020)
The first record of Turnera ulmifolia (Turneraceae) for Brazil is presented here. The species occurs mainly in SE Mexico, Central America and Caribbean islands, with only one record from South America. It can be recognized by ovoid and foliaceous prophylls, with serrate margins and laciniate appendages and/or extrafloral nectaries, showy flowers with yellow petals, without basal spot. Taxonomic comments, a distribution map and photographs of the species are provided.